Local Wisdom Media-Based Learning Model: Basic Competencies for Creative Economy Development in Social Sciences Subjects (Social Sciences) - Sudiadicita Panjaitan; Efendi Napitupulu; Sugiharto Sugiharto (RIRAI Publisher, 2024)
This research was motivated by the low learning outcomes of students in social studies learning in Class IX of SMP Negeri 1 Pahae Julu on Basic Competencies for Creative Economy Development. The aims of this research are 1) to find out the local wisdom-based learning model that has been developed and is valid for use in the social studies subject for Class IX of SMP Negeri 1 Pahae Julu, and 2) to find out the local wisdom-based learning model that can be developed and can be effective in improving student learning outcomes in the Social Sciences subject for Class IX of SMP Negeri 1 Pahae Julu. The research results show that the